Mal-estar y Psicoterapia. Un acercamiento transdisciplinario - Stornaiuolo Crosby, Martha (2015)
There are various perspectives of the world and the people, and several factors that make people suffer, the way DISCOMFORT is evidenced and healed. This study identifies the way this is evidenced in different fields in a traditional and modern Peru. Therefore, it is necessary to consider the social-historical location of the psychotherapeutic practice as well as of those who go to psychologist’s offices in order to understand better and help those who require our intervention.